Ekspresi Matrix Metalloproteinase-9 (MMP-9) pada Nodul Hiperplastik, Adenoma Folikuler dan Karsinoma Folikuler Tiroid - . Heriyawati; Imam Susilo (Majalah Patologi Indonesia, 2015)
Background Differential diagnosis of thyroid nodules can be problematic for pathologists and clinicians in routine examination. Especially, in differentiating hypercellular, hyperplastic nodule from follicular adenoma, as well as follicular adenoma from follicular carcinoma, because evidence of capsular and vascular invasion is necessary. Thus, ancilliary diagnostic marker may be useful along with histopathological examination of the nodules thyroid. Methods An analytic observational study with cross sectional approach was carried out. Study samples were patients with hyperplastic nodule, follicular adenoma and follicular carcinoma which were diagnosed histopathologically at the Laboratory of Anatomical Pathology of Dr. Soetomo Hospital during 2009-2011. Immunohistochemical examination was performed by using polyclonal antibody against MMP-9, a protein which has the ability to degrade extracellular matrix. Expression of MMP-9 was assessed semi quantitatively based on the percentage of tumor cells that showed imunoreactivity. Statistical differences were analyzed by using Kruskal-Wallis and Mann-Whitney test, with significance limit of p